Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
Option D.
[tex]\mathbf{\sqrt{3}} +1}[/tex]
Step-by-step explanation:
The given integral is:
[tex]\int^d_c \int ^{h_2(y)}_{h_1(y)} f(x,y)\ dx \ dy[/tex]
The intersection curves enclosed by the surfaces:
z = 2 - x² - y² and z = 2x + 2y
This implies that:
[tex]2x +2y = 2 - x^2- y^2[/tex]
[tex](x^2 + 2x) +(y^2 + 2y) = 2 \\ \\ (x+1)^2 + (y + 1)^2 = 4 --- (1)[/tex]
We will realize that the curve of this intersection is a circle which is centered at (-1, -1) of the radius 2.
So, from equation (1)
[tex](x + 1)^2 = 4 - (y + 1)^2[/tex]
x + 1 = ±[tex]\sqrt{4 - (y + 1)^2}[/tex]
[tex]x = -1 \pm \sqrt{4 - (y+1)^2}[/tex]
Now,
[tex]h_2 (y) = -1 + \sqrt{4 - (y +1)^2}[/tex] and [tex]h_1 (y) = -1 - \sqrt{4 - (y +1)^2}[/tex]
[tex]h_2(0) = -1 + \sqrt{4-1}[/tex]
[tex]h_2(0) = -1 + \sqrt{3}[/tex], and:
[tex]At \ \ (-1, -1); \\ \\ z = 2 - (-1)^2 - (-1)^2 \\ \\ z = 2 - 1 - 1 \\ \\ z = 0[/tex]
and
[tex]z = 2x + 2y \\ \\ z = 2(-1) + 2 (-1) \\ \\ z = -2 + (-2) \\ \\ z = -4[/tex]
The surface z = 2-x²-y² lies above z = 2x + 2y in the region of intersection
∴
[tex]f(x,y) = (2 - x^2 - y^2) - (2x + 2y) \\ \\ f(0,0) = 2 - 0 \\ \\ f(0,0) = 2[/tex]
So, h₂ (0) + f(0,0) = [tex]\sqrt{3}} - 1 + 2[/tex]
h₂ (0) + f(0,0) = [tex]\mathbf{\sqrt{3}} +1}[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.